Wave propagation in coastal waters - Koh, Rachel (2015)
The present study examines the damping of surface waves in the presence of viscoelastic bottom mud. To do so, a laboratory model was used with the bottom mud as a viscoelastic layer and the top water column using tap water. A material known as Polydimethylsiloxane (PDMS) was used to model the bottom mud layer. PDMS is readily available in the market and is made using two chemicals, an elastomer base and curing agent, which will undergo chemical reactions when combined to form a flexible and transparent product. The PDMS layer can have its viscoelastic properties readily altered by varying the amount of curing agent added to the mixture. With a fixed depth of mud sample at the bottom of a small wave tank, a fixed depth of water was added above. The set up was subjected to forcing using a rocking mechanism. A total of six experiments were studied over three forcing frequencies. Discussions of the experiments have been divided into two parts, namely those subjected to constant oscillatory motion and during decay of waves. Results of rheometer tests revealed that samples with low percentage of curing agent added were more viscous, and an increase in amount of curing agent added produced a sample with greater elasticity. By analysing the wave heights produced during steady state oscillation, experimental results indicated that the amount of energy dissipation within the water-mud system increased with the depth of water in the tank as well as the viscosity of the bottom layer. During the attenuation of waves, the decline in wave heights with the fastest rates occurred with the most viscous layers. However, the depth of water in the system and the viscoelastic properties of the bottom layer were not the only factors that can affect the resulting wave heights. The complex interactions between the fluid and the mud can contribute to the loss in energy within the system and cause slight discrepancies from the trend in the data obtained.